A Framework for Mobile Grid Environments based on Semantic Integration of Ontologies and Workflow-based Applications - Silva, A. P.C.; Borges, V. C.M.; Dantas, M. A.R. (INFOCOMP Journal of Computer Science, 2008)
One of objectives of the mobile grid infrastructure is become possible that the mobile user can use the computational power available in computational grids for solving complex problems. However, the majority of researches that search the interaction between mobile devices and grid computing do not provide a mechanism more automated and coordinated for submission and monitoring of several tasks that work cooperatively to solve a single problem. Additionally, none of these researches consider different forms that resources are described for the virtual organizations that compose the grid to select the resources more appropriate to execute these tasks. Therefore, in this paper is presented a framework that it treats these aspects. This framework uses the approach of integration semantics of multiple ontologies and the workflow mechanism, allowing a selection more omnibus of resources appropriate for execution of tasks of an automatized and controlled way more in the grid. A case study and experimental results demonstrated that framework enables: a selection of the resources more appropriate of different organizations for the execution of an application submitted from a mobile device and less power consumption of battery of these devices during the application submission and monitoring.